PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA PT MASKAPAI REASURANSI INDONESIA TBK - Dadang Kurnia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The purpose of this study was to determine the effect of service quality and corporate image on customer satisfaction at PT Airlines Reasurance Indonesia Tbk, both partially and simultaneously. The research method used is quantitative with descriptive explanation. The analytical method used is multiple linear regression analysis with a sample of 118 and the sampling technique used is Accidental Sampling. The systematic analysis consists of descriptive analysis, validity test, reliability test, classic assumption test, partial test, simultaneous test and coefficient of determination test. The results showed that service quality was more representative of satisfaction. Whereas corporate image only affects perception, therefore its effect on satisfaction is small